Sulfur-doped nanoporous carbon spheres with ultrahigh specific surface area and high electrochemical activity for supercapacitor - Liu, S.; Cai, Y.; Zhao, X.; Liang, Y.; Zheng, M.; Hu, H.; Dong, H.; Jiang, San Ping; Liu, Y.; Xiao, Yong (Elsevier SA, 2017)
© 2017 Development of facile and scalable synthesis process for the fabrication of nanoporous carbon materials with large specific surface areas, well-defined nanostructure, and high electrochemical activity is critical for the high performance energy storage applications. The key issue is the dedicated balance between the ultrahigh surface area and highly porous but interconnected nanostructure. Here, we demonstrate the fabrication of new sulfur doped nanoporous carbon sphere (S-NCS) with the ultrahigh surface area up to 3357 m 2 g -1 via a high-temperature hydrothermal carbonization and subsequent KOH activation process. The as-prepared S-NCS which integrates the advantages of ultrahigh porous structure, well-defined nanospherical and modification of heteroatom displays excellent electrochemical performance. The best performance is obtained on S-NCS prepared by the hydrothermal carbonization of sublimed sulfur and glucose, S-NCS-4, reaching a high specific capacitance (405 F g -1 at a current density of 0.5 A g -1 ) and outstanding cycle stability. Moreover, the symmetric supercapacitor is assembled by S-NCS-4 displays a superior energy density of 53.5 Wh kg -1 at the power density of 74.2 W kg -1 in 1.0 M LiPF 6 EC/DEC. The synthesis method is simple and scalable, providing a new route to prepare highly porous and heteroatom-doped nanoporous carbon spheres for high performance energy storage applications.